Faktor Faktor Yang Mempengaruhi Return Saham pada Perusahaan LQ 45 Periode 2020-2021 - Fauzan Indra; Yuli Chomsatu Samrotun (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
A stock return is a profit made from an investment determined by dividing the current period's stock price by the preceding period's stock price. The purpose of this research is to analyze and assess the influence of profitability, liquidity, leverage, firm size, and earnings per share (EPS) on stock returns. This research looks at LQ 45 enterprises that will be listed on the Indonesia Stock Exchange (IDX) in 2020 and 2021. Purposive sampling was utilized for the sampling, with a total sample size of 28 businesses. To examine the gathered data, several linear regression analytic methodologies were applied. According to the conclusions of this study, profitability and profits per share (EPS) have a considerable impact on stock returns. However, liquidity, leverage, and firm size do not have a significant effect on firm value.